Educación bilingüe en el sistema educativo intermedio: perspectiva comparada entre Brasil y Perú - Aranibar Ramos, Edgar Romario; Olarte Pacco, Miguel Angel Demetrio; Barbosa de Lima, Fabio (Pontificia Universidad Católica del Perú, 2025)
In the vast South American region, profound cultural and linguistic diversity gives rise to striking educational contrasts. This study aims to compare bilingual educational policies and practices in Brazil and Peru, exploring their normative and historical foundations, as well as the attention given to indigenous communities. The importance of analysing socio-educational dynamics in multicultural and multilingual environments is highlighted, along with the promotion of language and traditional integration in educational structures. Both challenges and possibilities are identified in the implementation of bilingual educational programmes in both nations. Ultimately, it underlines the urgent need to establish educational policies and methods that recognise and value the multiplicity of languages and traditions, aiming to foster equity and holistic development of individuals in pluricultural societies.

En la vasta región sudamericana, la profunda diversidad cultural y lingüística da lugar a notables contrastes educativos. Este estudio propone comparar las políticas y prácticas educativas bilingües en Brasil y Perú, explorando sus fundamentos normativos e históricos, así como la atención dispensada a las comunidades indígenas. Se destaca la importancia del análisis de las dinámicas socioeducativas en entornos multiculturales y plurilingües, junto con la promoción de la integración idiomática y tradicional en las estructuras de enseñanza. Se identifican tanto desafíos como posibilidades en la aplicación de programas educativos bilingües en ambas naciones. En última instancia, se subraya la necesidad apremiante de establecer normativas y métodos pedagógicos que reconozcan y valoren la multiplicidad de lenguas y tradiciones, aspirando a fomentar la equidad y desarrollo integral de los individuos en sociedades pluriculturales.

Na vasta região da América do Sul, a profunda diversidade cultural e linguística dá origem a contrastes educacionais impressionantes. Este estudo tem como objetivo comparar as políticas e práticas educacionais bilíngues no Brasil e no Peru, explorando seus fundamentos normativos e históricos, bem como a atenção dada às comunidades indígenas. Destaca-se a importância de analisar a dinâmica socioeducacional em ambientes multiculturais e multilíngues, juntamente com a promoção da integração de idiomas e tradições nas estruturas educacionais. Tanto os desafios quanto as possibilidades são identificados na implementação de programas educacionais bilíngues em ambas as nações. Por fim, destaca-se a necessidade urgente de estabelecer políticas e métodos educacionais que reconheçam e valorizem a multiplicidade de idiomas e tradições, com o objetivo de promover a equidade e o desenvolvimento holístico dos indivíduos em sociedades pluriculturais.
Bilingual education in the Intermediate Educational System: comparative perspective between Brazil and Peru
Educação bilíngue no Sistema Educacional Intermediário: perspectiva comparativa entre Brasil e Peru
Keywords: Linguistic diversity; Cultural inclusion; Indigenous communities; Educational challenges; Educational equity; Diversidad lingüística; Inclusión cultural; Comunidades indígenas; Desafíos educativos; Equidad educativa; Diversidade linguística; Inclusão cultural; Comunidades indígenas; Desafios educacionais; Equidade educativa; https://purl.org/pe-repo/ocde/ford#5.03.00